Temporality and transformation in training (Praxis Educativa, 2024)
Temporality in training processes is a topic rarely addressed in the bibliography. In this work, it asumes special interest in order to adresss the transformations that take place in trainers of trainers who undergo a training process. The work is part of a UBA research project in which 9 teacher trainers, participants in a clinical-type training device, are taken as key informants. From a qualitative and hermeneutic methodological strategy, the Constant Comparative Method (Strauss & Corbin, 2002) was applied in two moments: 1: final group meeting of the training workshop; 2: individual interviews with each participant one month later. The analysis creates a system of categories to record expectations, value judgments and transformations that they identify. In light of psychoanalytic concepts, hypotheses are developed that allow the concept of temporality to be prioritized in trainig processes.
Keywords: proffesional development - teacher educator training - skills development - attitude change - qualitative analysis